A Spatiotemporal analysis of photovoltaic electricity storage potential in electric vehicles - Jeannin, Noémie; Dumoulin, Jérémy; Pena-Bello, Alejandro; Wannier, David; Wyrsch, Nicolas; Ballif, Christophe (International Journal of Sustainable Energy Planning and Management, 2025)
Decarbonizing mobility and integrating more renewable sources in electricity production are necessary levers to meet the climate targets. Coupling electric vehicle (EV) charging with photovoltaic (PV) electricity generation could help to provide clean electricity for charging EVs and provide flexibility storage to PV installations. The batteries of the vehicles can then be discharged into the grid to support the electricity supply during periods of high demand. This study uses a GIS-based methodology to analyse the mobility needs of the European population and estimates the charging needs of an electrified vehicle fleet. Charging scenarios are then applied to distribute the charging needs between home, work, and point of interest to quantify the charging demand both in space by hectare and in time by hour. The charging load curves are then compared to a typical PV production to estimate the amount of PV electricity that can be stored locally in the EVs. Considering two charging scenarios (comfort and flexible charging) the spatio-temporal methodology was applied to three cities with varying solar irradiance and mobility patterns: Aalborg (Denmark), Bern (Switzerland), and Palermo (Italy). Results show that 10% of the building footprint covered with PV can cover from 53% (in Alborg) to 61% (in Bern) of the charging need over a year. EVs and PV electricity together can reduce the CO2 emission related to private cars of 17 to 28% by 2035 compared to the current fuel-based vehicle fleet.